Leiomyosarcoma of the Inferior Vena Cava: A Case Report of Complete and Sustained Response with Trabectedin - Cruz, André (2016)
Inferior vena cava leiomyosarcoma is a very rare tumor, accounting for only 0.5% of all soft tissue sarcomas. As the other leyomiosarcomas of vascular origin, they have a poor prognosis, and radical resection with surgical margins free of tumor is the only potentially curative treatment. We present a case of a 46 year-old woman with metastatic inferior vena cava leiomyosarcoma who progressed after anthracyclines and ifosfamide and achieved a complete and sustained response with trabectedin. Beyond progression, the patient started third line treatment with pazopanib. A brief review of literature is also given. This case supports the efectiveness of a recent therapeutic agent, with an impressive progression-free survival in a recurrent metastatic inferior vena cava leiomyosarcoma.